2014
DOI: 10.1002/bit.25444
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic engineering of 3‐hydroxypropionic acid biosynthesis in Escherichia coli

Abstract: 3-Hydroxypropionic acid (3-HP) can be produced in microorganisms as a versatile platform chemical. However, owing to the toxicity of the intermediate product 3-hydroxypropionaldehyde (3-HPA), the minimization of 3-HPA accumulation is critical for enhancing the productivity of 3-HP. In this study, we identified a novel aldehyde dehydrogenase, GabD4 from Cupriavidus necator, and found that it possessed the highest enzyme activity toward 3-HPA reported to date. To augment the activity of GabD4, several variants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(58 citation statements)
references
References 30 publications
1
55
0
1
Order By: Relevance
“…A recent study has demonstrated that the second enzyme is crucial for 3-HP production 168 Food biotechnology as the accumulation of the intermediate product 3-HPA is toxic to the host cells [27 ]. By selecting the most efficient aldehyde dehydrogenase, GabD4 derived from Cupriavidus necator, combined with directed mutagenesis this enzyme activity was further increased and the highest 3-HP titer and productivity was achieved, up to 71.9 g/L of 3-HP with a productivity of 1.8 g/L/h using glucose and glycerol as co-carbon sources.…”
Section: Production Of 3-hp From Glycerolmentioning
confidence: 99%
“…A recent study has demonstrated that the second enzyme is crucial for 3-HP production 168 Food biotechnology as the accumulation of the intermediate product 3-HPA is toxic to the host cells [27 ]. By selecting the most efficient aldehyde dehydrogenase, GabD4 derived from Cupriavidus necator, combined with directed mutagenesis this enzyme activity was further increased and the highest 3-HP titer and productivity was achieved, up to 71.9 g/L of 3-HP with a productivity of 1.8 g/L/h using glucose and glycerol as co-carbon sources.…”
Section: Production Of 3-hp From Glycerolmentioning
confidence: 99%
“…One solution to the problem could be the selection of an efficient aldehyde dehydrogenase that would rapidly act on 3-hydroxypropionaldehyde and convert it to 3HP. Based on this strategy, Chu et al [34] tried 17 candidate aldehyde dehydrogenases for their activity against 3-hydroxypropionaldehyde, with the gabD4 from Cupriavidus necator turning out to be the most effective one. In an attempt to further improve the aldehyde dehydrogenase selected, the authors performed site-directed and saturation mutagenesis, based on homologous modeling.…”
Section: Engineering Of E Coli Cells For the Conversion Of Glycerol mentioning
confidence: 99%
“…The second highest productivity of 3-HP in Table 2 is 1.8 g*L -1 *h -1 [20]. In the study a novel aldehyde dehydrogenase, GabD4 from Cupriavidus necator was identified and found that it possessed the highest enzyme activity on 3-HPA reported to [43] date.…”
Section: Highest 3-hp Productivitymentioning
confidence: 98%
“…The former strategy would reduce the overall rate of production. Therefore, the latter is considered more desirable [10,20].…”
Section: Toxicity Of 3-hpamentioning
confidence: 99%
See 1 more Smart Citation